Educação ambiental e as dimensões cognitiva e afetiva do trabalho com valores: produzindo sentidos - Degasperi, Thais Cristiane; Bonotto, Dalva Maria Bianchini (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2017)
Abstract: From the context of the socio-environmental crisis, we envisage the contribution of the Environmental Education as a way of confronting and proposing of new ways for the relation between society and nature. We propose the reintroduction and/or construction of new values that must involve affective and reflective aspects in order to project new patterns of individual relations with the nature and society. In a qualitative perspective, we analyzed the meaning making in the dialogues in episodes of teaching that occurred between the teacher and the students regarding environmental themes and values especially considering the cognitive and affective dimensions. We verified that the articulation among these dimensions have resulted in a significant work with values, amplifying the probabilities of its construction. Between the aesthetic appreciation of a green area and the proposition of a dilemma, there is an intentionality of the teacher, limits and possibilities of these activities with the senses that are produced, constituting novel ways of speaking about the relationship between society and nature.

Resumo: A partir do contexto de crise socioambiental, vislumbramos a contribuição da Educação Ambiental como forma de enfrentamento e proposição de novos caminhos para a relação sociedade-natureza. Propomos o resgate e/ou construção de novos valores, que devem envolver afetos e reflexões, projetando-se em novos padrões de relação do indivíduo com o ambiente e a sociedade. Em uma perspectiva qualitativa, analisamos os sentidos produzidos nos diálogos empreendidos em episódios de ensino ocorridos entre professora e alunos a respeito da temática ambiental e valores, considerando, especialmente, as dimensões cognitiva e afetiva. Verificamos que a articulação dessas dimensões, nos episódios, implicou em um trabalho com valores significativo, ampliando as possibilidades de sua construção. Entre a apreciação estética de uma área verde e a proposição de um dilema a seu respeito há a intencionalidade do docente, limites e possibilidades dessas atividades, com os sentidos que nelas são produzidos, constituindo-se novos discursos para a relação sociedade-natureza.
Environmental education and the cognitive and affective dimensions from the work with values: the production of meanings
Keywords: Environmental education; Cognition; Affectivity; Meaning-making; Educação ambiental; Cognição; Afetividade; Produção de sentidos